SEMANTIC PREFERENCE AND SEMANTIC PROSODY OF THE COLLOCATION OF IRAN IN TRUMP'S SOCIAL MEDIA - Suhaili, Ahmad; Sayogie, Frans; Susanto, Ashabul Kahfi (Universitas Islam Negeri Sunan Gunung Djati, 2025)
The relationship between the United States and Iran has long been marked by tensions, particularly over nuclear issues, economic sanctions, and regional conflicts. Under the Trump administration, these tensions escalated further, especially after the U.S. withdrew from the Joint Comprehensive Plan of Action (JCPOA) in 2018. Trump's rhetoric on social media reflected his administration’s hardline stance toward Iran, making it a critical subject of linguistic analysis. The study aimed to investigate the semantic preference and semantic prosody of the collocation of Iran in Trump’s social media. This research focuses on a corpus-based study of Trump’s social media posts, compiled exclusively from those made during his presidency, from January 2017 to January 2021. The corpus dataset of @realdonaldtrump was taken from the trumptweetarchiever.com site, official Facebook and Instagram accounts from January 2017 to January 2021, which were collected in the form of a text compilation with the date containing all tweets and posts related to the country of Iran, then what are the lexicogrammatical elements that accompany it, as well as semantic categories involved in the collocation of these words. Considering the results of the MI (mutual information) score, the single keyword Iran in Trump's social media corpus tends to be associated with collocations related to the issue of economic sanctions, namely the nuclear deal. The results indicated that the keyword Iran carries a predominantly negative semantic preference, although not all keywords associated with Iran hold a positive meaning upon evaluating the concordance. The study concluded that Trump tends to portray the word Iran in a negative light.